2022
DOI: 10.1007/s40145-022-0575-5
|View full text |Cite
|
Sign up to set email alerts
|

21-Component compositionally complex ceramics: Discovery of ultrahigh-entropy weberite and fergusonite phases and a pyrochlore-weberite transition

Abstract: Two new high-entropy ceramics (HECs) in the weberite and fergusonite structures, along with the unexpected formation of ordered pyrochlore phases with ultrahigh-entropy compositions and an abrupt pyrochlore-weberite transition, are discovered in a 21-component oxide system. While the Gibbs phase rule allows 21 equilibrium phases, 9 out of the 13 compositions examined possess single HEC phases (with ultrahigh ideal configurational entropies: ∼2.7kB per cation or higher on one sublattice in most cases). Notably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 78 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…Specially, RE 3 Nb/TaO 7 oxides exhibit excellent thermal insulation (thermal conductivity (k) = 0.92.1 W•m −1 •K −1 at 25900 ℃) at both low and high temperatures, as well as outstanding phase stability, except that phase transitions are found in Sm 3 TaO 7 and Sm 3 NbO 7 ceramics in Refs. [3,10,17,23,24]. Furthermore, hightemperature protective coatings require outstanding comprehensive properties to maintain their service performance [2830].…”
Section: Introduction mentioning
confidence: 99%
See 2 more Smart Citations
“…Specially, RE 3 Nb/TaO 7 oxides exhibit excellent thermal insulation (thermal conductivity (k) = 0.92.1 W•m −1 •K −1 at 25900 ℃) at both low and high temperatures, as well as outstanding phase stability, except that phase transitions are found in Sm 3 TaO 7 and Sm 3 NbO 7 ceramics in Refs. [3,10,17,23,24]. Furthermore, hightemperature protective coatings require outstanding comprehensive properties to maintain their service performance [2830].…”
Section: Introduction mentioning
confidence: 99%
“…The fluorite RE 3 Nb/TaO 7 HEOs have been studied to optimize their properties. For example, Qin et al [10] reported the structural transition and property evolution of RE 3 Nb/TaO 7 HEOs with a fluorite structure, Zhao et al [17] reported the mechanical property enhancements of fluorite RE 3 NbO 7 HEOs, and Chen et al [3] reported the limit thermal conductivity of fluorite-type RE 3 NbO 7 HEOs. Clearly, most studies have focused on HEOs of fluorite-type RE 3 Nb/TaO 7 , whereas little attention has been paid to weberite-type RE 3 Nb/TaO 7 .…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the concept of high-entropy materials and the four major effects (high configurational entropy, severe lattice distortion, sluggish diffusion, and "cocktail" effect) are further extended to the field of ceramics [3][4][5]. Highentropy ceramics with various excellent properties have been developed successively [6][7][8][9][10][11], and the compositionally complex ceramics (CCCs) with more flexible principal element numbers and content range are further proposed [12,13]. Research on high-entropy ceramics has included a variety of crystal structures such as rock salt structure, pyrochlore structure, perovskite structure, argyrodite structure, fluorite structure, spinel structure, hexagonal CrSi 2 -type structure, hexagonal AlB 2 -type structure, aluminates, silicates, and borides [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Highentropy ceramics with various excellent properties have been developed successively [6][7][8][9][10][11], and the compositionally complex ceramics (CCCs) with more flexible principal element numbers and content range are further proposed [12,13]. Research on high-entropy ceramics has included a variety of crystal structures such as rock salt structure, pyrochlore structure, perovskite structure, argyrodite structure, fluorite structure, spinel structure, hexagonal CrSi 2 -type structure, hexagonal AlB 2 -type structure, aluminates, silicates, and borides [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, to the best of our knowledge, there is no research on the fabrication of the high-entropy ceramics with the pseudobrookite structure.…”
Section: Introductionmentioning
confidence: 99%